Observations of a species‐record deep dive by a central Pacific female scalloped hammerhead shark (Sphyrna lewini). Issue 1 (7th June 2022) - Anderson, James M.; Rex, Patrick T.; Maloney, Kelsey; Johnston, Mark; Verbeck, Deron; Allen, Neil; Holland, Kim
Abstract: A female scalloped hammerhead shark ( Sphyrna lewini ) conducted a species record deep dive to 1240 m in coastal‐pelagic waters off Hawaii Island. This extends the deepest known depth range of the species by over 200 m (650 ft) and highlights the question of the extent to which deep‐diving activity is mediated by physiological constraints, such as temperature and oxygen availability.